EFEK MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN MELALUI MEDIASI MANAJEMEN LABA - Hendrik ES Samosir; Christnova Hasugian; Sri Ida Royani Simanjuntak; Aldian Syahputra Perangin-angin (JURNAL LENTERA BISNIS, 2024)
The purpose of this study is as follows. To determine the effect of Good Corporate Governance/GCG (Institutional Ownership, Managerial Ownership, Board of Commissioners Size) on Financial Performance (ROA). To determine the effect of Good Corporate Governance/GCG (Institutional Ownership, Managerial Ownership, Board of Commissioners Size) on Earnings Management. To determine the effect of Earnings Management on Financial Performance (ROA). To determine the effect of Good Corporate Governance/GCG (Institutional Ownership, Managerial Ownership, Board of Commissioners Size) on Financial Performance (ROA) through Earnings Management. The research method is quantitative method, associative research. The results of the study did not show a significant effect of Institutional Ownership on Earnings Management. There was no significant effect of Institutional Ownership on ROA. There was no significant effect of Managerial Ownership on Earnings Management. There was no significant effect of Managerial Ownership on ROA. There was no significant effect of Earnings Management on ROA. There is no significant influence of the Size of the Board of Commissioners on ROA. There is a significant influence of the Size of the Board of Commissioners on ROA.